Neural networks and deep learning - Géron, Aurélien (O'Reilly, 2018)
"From Hands-on machine learning with Scikit-Learn and TensorFlow by Aurélien Géron"--Page 1 of cover.
"From Hands-on machine learning with Scikit-Learn and TensorFlow by Aurélien Géron"--Cover. - Date of publication from resource description page. - Includes bibliographical references. - Online resource; title from title page (Safari, viewed March 16, 2018)
Keywords: Machine learning; Artificial intelligence; Artificial Intelligence; Machine Learning; Apprentissage automatique; Intelligence artificielle; artificial intelligence